PENGARUH EFIKASI DIRI, MOTIVASI KERJA, DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN - Sutansi, Yunita Caroline; Widayati, Nurti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This study aims to determine the effect of self efficacy, work motivation, and work environment on the job satisfaction of employees of PT Interdesign Cipta Optima. This research was conducted at PT Interdesign Cipta Optima. The sample in this study used a purposive sampling technique, which amounted to 130 respondents. Collecting data using observation methods and questionnaires. The data analysis technique used is multiple regression analysis. The results showed that self efficacy and work motivation had no effect on job satisfaction. While work environment has an effect on job satisfaction.